A high-space-velocity SCR denitration catalyst for a gas generator set and a preparation method thereof
By combining the modified cordierite skeleton with hydrophobic V2O5-WO3/TiO2 catalyst, a high-speed SCR denitrification catalyst with high mechanical strength and high denitrification activity was prepared, which solved the problem of high NOx concentration in the flue gas of the gas gas generator set, and achieved the goal of achieving the It has efficient denitrification effect and environmentally friendly preparation process.
Patent Information
- Application Number
- CN202310740915.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-06-21
AI Technical Summary
The NOx concentration in the flue gas of the gas gas generator set is high, and the conventional SCR denitrification catalyst has low activity, which cannot meet the needs of high-speed and high-active denitrification.
A modified cordierite skeleton combined with a hydrophobic V2O5-WO3/TiO2 catalyst powder was used to prepare a high-speed SCR denitrification catalyst by pretreatment of titanate compound solution and vacuum drying to form a catalyst with high mechanical strength and high denitrification activity.
The high mechanical strength and high denitrification activity of high-speed SCR denitrification catalyst are achieved, which meets the treatment needs of high NOx concentration flue gas in the gas generator set, avoids defects caused by high temperature drying, and realizes energy-saving and environmental protection through condensation and reuse of organic solvents. Preparation process.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flue gas denitration, and particularly relates to a high-space-velocity SCR denitration catalyst for a gas generator set and a preparation method thereof. Background Art
[0002] Coalbed methane is called coal mine gas in coal mines. The main component of coalbed methane is methane. When the concentration of methane in the air reaches 5%-16%, it will explode when it encounters open flames. This is the root cause of coal mine gas explosion accidents. If coalbed methane is not used and is directly discharged into the atmosphere, its greenhouse effect is about 21 times that of carbon dioxide.
[0003] Gas power generation can not only effectively solve coal mine gas accidents and improve coal mine safety production conditions, but also help increase clean energy supply and reduce greenhouse gas emissions, achieving multiple goals of protecting life, protecting resources, and protecting the environment. However, due to its special structure, the gas generator set has a very high NOx concentration in the flue gas, ranging from 2000 to 8000 mg / Nm 3 NOx in flue gas is a highly polluting component that can cause acid rain and photochemical smog. 3 Selective catalytic reduction (SCR) denitrification technology as a reducing agent is the best choice for NOx treatment.
[0004] Since the NOx concentration in the flue gas of gas generator sets is too high and the unit structure is compact, the SCR denitration catalyst must have extremely high activity and small size, that is, the catalyst is required to operate at high space velocity and high activity for denitration. Conventional mature commercial SCR denitration catalysts cannot meet the high space velocity and high activity denitration requirements of gas generator sets due to their low activity. Summary of the invention
[0005] The object of the present invention is to provide a high-space-velocity SCR denitration catalyst for a gas generator set and a preparation method thereof, which can meet the high-space-velocity use of the catalyst.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for preparing a high-space-velocity SCR denitration catalyst for a gas generator set comprises the following steps:
[0008] Step 1: pretreatment of the cordierite skeleton: soaking the modified cordierite skeleton in a titanate compound solution, and then drying the soaked modified cordierite;
[0009] Step 2: Impregnation of catalyst active powder slurry: impregnating the modified cordierite skeleton dried in step 1 with hydrophobically modified catalyst active powder slurry to obtain a catalyst precursor, wherein the catalyst active powder slurry contains 35% to 50% of hydrophobically modified catalyst powder, 1% to 3% of silica sol and 43% to 64% of an organic solvent;
[0010] Step 3: vacuum drying: vacuum drying the catalyst precursor obtained in step 2;
[0011] Step 4: high temperature calcination: calcine the catalyst precursor dried in step 3 to obtain a high space velocity SCR denitrification catalyst.
[0012] Preferably, in step one, a titanate compound is dissolved in deionized water to form a titanate compound solution, and the modified cordierite skeleton is immersed in the titanate compound solution for 2 hours, and then the modified cordierite skeleton is taken out and dried at 110° C. for 3 hours.
[0013] Preferably, the mass ratio of the titanate compound in the titanate compound solution is 60% to 80%; the titanate compound is one of isopropyl di(dioctylphosphite) titanate or isopropyl trioleyl titanate.
[0014] Preferably, the modified cordierite skeleton is a honeycomb body with 80 to 108 pores, and the pore volume of the modified cordierite skeleton is 0.05 to 0.2 ml / g.
[0015] Preferably, the modified cordierite framework comprises 5.5% MgO, 13.5% Al 2 O 3 and 81% SiO 2 .
[0016] Preferably, the step (2) further includes the step of preparing a catalyst active powder slurry: weighing a hydrophobically modified catalyst active powder, dispersing it in an organic solvent and stirring it for 1 hour to form a solution A, then adding silica sol to the solution A to form a mixed solution B, grinding the mixed solution B for 2 hours to obtain a catalyst active powder slurry.
[0017] Preferably, the hydrophobically modified catalyst active powder is a hydrophobic V 2 O 5 -WO 3 / TiO 2 Pink, V 2 O 5 -WO 3 / TiO 2The mass ratios of are 1.9%-4.0% / 94.1% respectively; the silica sol is alkaline silica sol, and the solid content of the silica sol is 40%; and the organic solvent is dimethylformamide (DMF, CAS: 68-12-2).
[0018] Preferably, in step three, the volatilized organic solvent is condensed by a condensing device; the vacuum drying temperature is 75° C., the vacuum pressure is -0.03 MPa, and the vacuum drying time is 5 hours.
[0019] Preferably, in step 4, the maximum calcination temperature is 550° C., and the maximum calcination time is 2 h.
[0020] A high-space-velocity SCR denitration catalyst for a gas generator set is prepared by adopting the above-mentioned preparation method.
[0021] The invention has the following beneficial effects:
[0022] The present invention aims at the flue gas conditions of gas generator sets and prepares a high-performance SCR denitration catalyst that meets the requirements for flue gas denitration of gas generator sets. The catalyst has the following excellent properties:
[0023] (1) High mechanical strength. Modified cordierite is used. The modified cordierite has a pore volume of 0.05-0.2 ml / g. When the catalyst powder slurry is impregnated into the modified cordierite, the slurry can enter the modified cordierite pores, thereby forming a "chimeric" effect between the catalyst layer and the modified cordierite, and strengthening the adhesion between the catalyst layer and the cordierite skeleton; the modified cordierite skeleton is pretreated with a titanate solution, and the hydrophobic group V 2 O 5 -WO 3 / TiO 2 The catalyst layer forms a chemical bond and interaction with the modified cordierite skeleton treated with titanate, further increasing the bonding force between the catalyst layer and the modified cordierite skeleton, thus satisfying the high space velocity use of the catalyst;
[0024] (2) High denitrification activity, using hydrophobic group V 2 O 5 -WO 3 / TiO 2 The powder is mixed with a low surface tension organic solvent to prepare a catalyst powder slurry, and the hydrophobic base V 2 O 5 -WO 3 / TiO 2The powder is highly dispersed in the organic solvent, ensuring that the catalytically active powder is evenly distributed on the cordierite skeleton and the catalytic components are highly dispersed, thereby improving the catalyst activity. At the same time, the selection of low surface tension organic solvents can quickly defoam the bubbles introduced during the slurry grinding process, avoiding the formation of catalytic layer shrinkage holes during the catalyst drying process, greatly improving the utilization rate of the catalyst powder on the cordierite skeleton per unit area, improving the catalyst denitrification activity, and meeting the requirements for high NOx concentration flue gas denitrification.
[0025] (3) The catalyst preparation process is energy-saving and environmentally friendly. The catalyst is dried at low temperature using vacuum drying equipment. This not only avoids defects such as "orange peel", "shrinkage" and "cracking" of the catalyst layer caused by high-temperature drying, but also uses condensation equipment to condense and reuse the volatile organic solvent during the low-temperature drying vacuum process, thereby achieving the purpose of resource recycling. DETAILED DESCRIPTION
[0026] The present invention is further described below in conjunction with specific embodiments.
[0027] Example 1
[0028] The method for preparing a high-space-velocity SCR denitration catalyst for a gas generator set described in this embodiment comprises the following steps:
[0029] Step 1: Pretreatment of cordierite skeleton: Select 80-pore modified cordierite honeycomb as skeleton material, with external dimensions of 150mm*150mm*150mm and chemical composition of MgO, Al 2 O 3 and SiO 2 A mixture of MgO, Al 2 O 3 and SiO 2 The mass ratio is 5.5%:13.5%:81%, and the pore volume of modified cordierite is 0.17ml / g;
[0030] 80 g of isopropyl di(dioctylphosphite) titanate was dissolved in 20 g of deionized water to form a titanate compound solution, and the modified cordierite skeleton was immersed in the titanate compound solution for 2 hours, and then the modified cordierite skeleton was taken out and dried at 110° C. for 3 hours to complete the pretreatment of the modified cordierite skeleton;
[0031] Step 2: Impregnation of catalyst active powder slurry: Weigh 35 parts of conventional commercial hydrophobic V 2 O 5 -WO 3 / TiO 2 Powder (V 2 O 5 -WO 3 / TiO 2The mass ratio is 1.9%-4.0% / 94.1% respectively) dispersed in 62 parts of dimethylformamide (DMF, CAS: 68-12-2) to form a solution A, and then 3 parts of silica sol with a solid content of 40% are added to the solution A to form a mixed solution B, and the mixed solution B is ground for 2 hours using a sand mill to obtain a catalyst active powder slurry; the modified cordierite skeleton after drying in step 1 is immersed in the catalyst active powder slurry for 10 minutes to obtain a catalyst precursor, and the hydrophobic modified catalyst active powder slurry impregnation is completed;
[0032] Step 3: vacuum drying: vacuum drying the catalyst precursor obtained in step 2, the vacuum drying temperature is 75°C, the vacuum pressure is -0.03MPa, and the vacuum drying is performed for 5 hours, wherein the vacuum drying equipment is equipped with a condensing device, and the dried, volatilized and condensed dimethylformamide (DMF, CAS: 68-12-2) is reused in the preparation of the catalyst active powder slurry;
[0033] Step 4: High temperature calcination: The catalyst precursor dried in step 3 is calcined in a sintering furnace, the maximum calcination temperature is 550° C., and the maximum calcination time is 2 hours.
[0034] Example 2
[0035] The method for preparing a high-space-velocity SCR denitration catalyst for a gas generator set described in this embodiment comprises the following steps:
[0036] Step 1: Pretreatment of cordierite skeleton: Select 80-pore modified cordierite honeycomb as skeleton material, with external dimensions of 150mm*150mm*150mm and chemical composition of MgO, Al 2 O 3 and SiO 2 A mixture of MgO, Al 2 O 3 and SiO 2 The mass ratio is 5.5%:13.5%:81%, and the pore volume of modified cordierite is 0.17ml / g;
[0037] 60 g of isopropyl di(dioctylphosphite) titanate was dissolved in 40 g of deionized water to form a titanate compound solution, and the modified cordierite skeleton was immersed in the titanate compound solution for 2 hours, and then the modified cordierite skeleton was taken out and dried at 110° C. for 3 hours to complete the pretreatment of the modified cordierite skeleton;
[0038] Step 2: Impregnation of catalyst active powder slurry: Weigh 35 parts of conventional commercial hydrophobic V 2 O 5 -WO 3 / TiO 2 Powder (V 2 O5 -WO 3 / TiO 2 The mass ratio is 1.9%-4.0% / 94.1% respectively) dispersed in 62 parts of dimethylformamide (DMF, CAS: 68-12-2) to form a solution A, and then 3 parts of silica sol with a solid content of 40% are added to the solution A to form a mixed solution B, and the mixed solution B is ground for 2 hours using a sand mill to obtain a catalyst active powder slurry; the modified cordierite skeleton after drying in step 1 is immersed in the catalyst active powder slurry for 10 minutes to obtain a catalyst precursor, and the hydrophobic modified catalyst active powder slurry impregnation is completed;
[0039] Step 3: Vacuum drying: The catalyst precursor obtained in step 2 is vacuum dried at a temperature of 75°C and a vacuum pressure of -0.03 MPa for 5 h;
[0040] Step 4: High temperature calcination: The catalyst precursor dried in step 3 is calcined in a sintering furnace, the maximum calcination temperature is 550°C, and the maximum calcination time is 2h.
[0041] Comparative Example 1
[0042] Step 1: Pretreatment of cordierite skeleton: Select 80-pore modified cordierite honeycomb as skeleton material, with external dimensions of 150mm*150mm*150mm and chemical composition of MgO, Al 2 O 3 and SiO 2 A mixture of MgO, Al 2 O 3 and SiO 2 The mass ratio is 5.5%:13.5%:81%, and the pore volume of the modified cordierite is 0.17 ml / g;
[0043] The modified cordierite skeleton is placed in 100% deionized water and soaked for 2 hours, then the modified cordierite skeleton is taken out and dried at 110° C. for 3 hours to complete the pretreatment of the modified cordierite skeleton;
[0044] Step 2: Impregnation of catalyst active powder slurry: Weigh 35 parts of conventional commercial hydrophobic V 2 O 5 -WO 3 / TiO 2 Powder (V 2 O 5 -WO 3 / TiO 2The mass ratio is 1.9%-4.0% / 94.1% respectively) dispersed in 62 parts of dimethylformamide (DMF, CAS: 68-12-2) to form a solution A, and then 3 parts of silica sol with a solid content of 40% are added to the solution A to form a mixed solution B, and the mixed solution B is ground for 2 hours using a sand mill to obtain a catalyst active powder slurry; the modified cordierite skeleton after drying in step 1 is immersed in the catalyst active powder slurry for 10 minutes to obtain a catalyst precursor, and the hydrophobic modified catalyst active powder slurry impregnation is completed;
[0045] Step 3: Vacuum drying: The catalyst precursor obtained in step 2 is vacuum dried at a temperature of 75°C and a vacuum pressure of -0.03 MPa for 5 h;
[0046] Step 4: High temperature calcination: The catalyst precursor dried in step 3 is calcined in a sintering furnace, the maximum calcination temperature is 550°C, and the maximum calcination time is 2h.
[0047] Example 3
[0048] The method for preparing a high-space-velocity SCR denitration catalyst for a gas generator set described in this embodiment comprises the following steps:
[0049] Step 1: Pretreatment of cordierite skeleton: Select 80-pore modified cordierite honeycomb as skeleton material, with external dimensions of 150mm*150mm*150mm and chemical composition of MgO, Al 2 O 3 and SiO 2 A mixture of MgO, Al 2 O 3 and SiO 2 The mass ratio is 5.5%:13.5%:81%, and the pore volume of the modified cordierite is 0.17 ml / g;
[0050] 60 g of isopropyl di(dioctylphosphite) titanate was dissolved in 20 g of deionized water to form a titanate compound solution, and the modified cordierite skeleton was immersed in the titanate compound solution for 2 hours, and then the modified cordierite skeleton was taken out and dried at 110° C. for 3 hours to complete the pretreatment of the modified cordierite skeleton;
[0051] Step 2: Impregnation of catalyst active powder slurry: Weigh 50 parts of conventional commercial hydrophobic V 2 O 5 -WO 3 / TiO 2 Powder (V 2 O 5 -WO 3 / TiO 2The mass ratio is 1.9%-4.0% / 94.1% respectively) dispersed in 49 parts of dimethylformamide (DMF, CAS: 68-12-2) to form a solution A, and then 1 part of silica sol with a solid content of 40% is added to the solution A to form a mixed solution B, and the mixed solution B is ground for 2 hours using a sand mill to obtain a catalyst active powder slurry; the modified cordierite skeleton after drying in step 1 is immersed in the catalyst active powder slurry for 10 minutes to obtain a catalyst precursor, and the hydrophobic modified catalyst active powder slurry impregnation is completed;
[0052] Step 3: Vacuum drying: The catalyst precursor obtained in step 2 is vacuum dried at a temperature of 75°C and a vacuum pressure of -0.03 MPa for 5 h;
[0053] Step 4: High temperature calcination: The catalyst precursor dried in step 3 is calcined in a sintering furnace, the maximum calcination temperature is 550°C, and the maximum calcination time is 2h.
[0054] Example 4
[0055] The method for preparing a high-space-velocity SCR denitration catalyst for a gas generator set described in this embodiment comprises the following steps:
[0056] Step 1: Pretreatment of cordierite skeleton: Select 80-pore modified cordierite honeycomb as skeleton material, with external dimensions of 150mm*150mm*150mm and chemical composition of MgO, Al 2 O 3 and SiO 2 A mixture of MgO, Al 2 O 3 and SiO 2 The mass ratio is 5.5%:13.5%:81%, and the pore volume of the modified cordierite is 0.17 ml / g;
[0057] 60 g of isopropyl trioleyl titanate was dissolved in 20 g of deionized water to form a titanate compound solution, and the modified cordierite skeleton was immersed in the titanate compound solution for 2 hours, and then the modified cordierite skeleton was taken out and dried at 110° C. for 3 hours to complete the pretreatment of the modified cordierite skeleton;
[0058] Step 2: Impregnation of catalyst active powder slurry: Weigh 50 parts of conventional commercial hydrophobic V 2 O 5 -WO 3 / TiO 2 Powder (V 2 O 5 -WO 3 / TiO 2The mass ratio is 1.9%-4.0% / 94.1% respectively) dispersed in 49 parts of dimethylformamide (DMF, CAS: 68-12-2) to form a solution A, and then 1 part of silica sol with a solid content of 40% is added to the solution A to form a mixed solution B, and the mixed solution B is ground for 2 hours using a sand mill to obtain a catalyst active powder slurry; the modified cordierite skeleton after drying in step 1 is immersed in the catalyst active powder slurry for 10 minutes to obtain a catalyst precursor, and the hydrophobic modified catalyst active powder slurry impregnation is completed;
[0059] Step 3: Vacuum drying: The catalyst precursor obtained in step 2 is vacuum dried at a temperature of 75°C and a vacuum pressure of -0.03 MPa for 5 h;
[0060] Step 4: High temperature calcination: The catalyst precursor dried in step 3 is calcined in a sintering furnace, the maximum calcination temperature is 550°C, and the maximum calcination time is 2h.
[0061] Example 5
[0062] The method for preparing a high-space-velocity SCR denitration catalyst for a gas generator set described in this embodiment comprises the following steps:
[0063] Step 1: Pretreatment of cordierite skeleton: Select 80-pore modified cordierite honeycomb as skeleton material, with external dimensions of 150mm*150mm*150mm and chemical composition of MgO, Al 2 O 3 and SiO 2 A mixture of MgO, Al 2 O 3 and SiO 2 The mass ratio is 5.5%:13.5%:81%, and the pore volume of the modified cordierite is 0.05 ml / g;
[0064] 60 g of isopropyl trioleyl titanate was dissolved in 20 g of deionized water to form a titanate compound solution, and the modified cordierite skeleton was immersed in the titanate compound solution for 2 hours, and then the modified cordierite skeleton was taken out and dried at 110° C. for 3 hours to complete the pretreatment of the modified cordierite skeleton;
[0065] Step 2: Impregnation of catalyst active powder slurry: Weigh 50 parts of conventional commercial hydrophobic V 2 O 5 -WO 3 / TiO 2 Powder (V 2 O 5 -WO 3 / TiO 2The mass ratio is 1.9%-4.0% / 94.1% respectively) dispersed in 49 parts of dimethylformamide (DMF, CAS: 68-12-2) to form a solution A, and then 1 part of silica sol with a solid content of 40% is added to the solution A to form a mixed solution B, and the mixed solution B is ground for 2 hours using a sand mill to obtain a catalyst active powder slurry; the modified cordierite skeleton after drying in step 1 is immersed in the catalyst active powder slurry for 10 minutes to obtain a catalyst precursor, and the hydrophobic modified catalyst active powder slurry impregnation is completed;
[0066] Step 3: Vacuum drying: The catalyst precursor obtained in step 2 is vacuum dried at a temperature of 75°C and a vacuum pressure of -0.03 MPa for 5 h;
[0067] Step 4: High temperature calcination: The catalyst precursor dried in step 3 is calcined in a sintering furnace, the maximum calcination temperature is 550°C, and the maximum calcination time is 2h.
[0068] Comparative Example 2
[0069] Step 1: Pretreatment of cordierite skeleton: Select 80-pore modified cordierite honeycomb as skeleton material, with external dimensions of 150mm*150mm*150mm and chemical composition of MgO, Al 2 O 3 and SiO 2 A mixture of MgO, Al 2 O 3 and SiO 2 The mass ratio is 5.5%:13.5%:81%, and the pore volume of the modified cordierite is 0.05 ml / g;
[0070] 60 g of isopropyl trioleyl titanate was dissolved in 20 g of deionized water to form a titanate compound solution, and the modified cordierite skeleton was immersed in the titanate compound solution for 2 hours, and then the modified cordierite skeleton was taken out and dried at 110° C. for 3 hours to complete the pretreatment of the modified cordierite skeleton;
[0071] Step 2: Impregnation of catalyst active powder slurry: Weigh 50 parts of conventional commercial hydrophilic V 2 O 5 -WO 3 / TiO 2 Powder (V 2 O 5 -WO 3 / TiO 2The mass ratio is 1.9%-4.0% / 94.1% respectively) dispersed in 49 parts of deionized water to form a solution A, and then 1 part of silica sol with a solid content of 40% is added to the solution A to form a mixed solution B, and the mixed solution B is ground for 2 hours using a sand mill to obtain a catalyst active powder slurry; the modified cordierite skeleton after drying in step 1 is immersed in the catalyst active powder slurry for 10 minutes to obtain a catalyst precursor, and the hydrophobic modified catalyst active powder slurry is impregnated;
[0072] Step 3: Vacuum drying: The catalyst precursor obtained in step 2 is vacuum dried at a temperature of 75°C and a vacuum pressure of -0.03 MPa for 5 h;
[0073] Step 4: High temperature calcination: The catalyst precursor dried in step 3 is calcined in a sintering furnace, the maximum calcination temperature is 550°C, and the maximum calcination time is 2h.
[0074] Example 6
[0075] The method for preparing a high-space-velocity SCR denitration catalyst for a gas generator set described in this embodiment comprises the following steps:
[0076] Step 1: Pretreatment of cordierite skeleton: Select 108-hole modified cordierite honeycomb as skeleton material, with external dimensions of 150mm*150mm*150mm, and chemical composition of MgO, Al 2 O 3 and SiO 2 A mixture of MgO, Al 2 O 3 and SiO 2 The mass ratio is 5.5%:13.5%:81%, and the pore volume of the modified cordierite is 0.05 ml / g;
[0077] 60 g of isopropyl trioleyl titanate was dissolved in 20 g of deionized water to form a titanate compound solution, and the modified cordierite skeleton was immersed in the titanate compound solution for 2 hours, and then the modified cordierite skeleton was taken out and dried at 110° C. for 3 hours to complete the pretreatment of the modified cordierite skeleton;
[0078] Step 2: Impregnation of catalyst active powder slurry: Weigh 50 parts of conventional commercial hydrophobic V 2 O 5 -WO 3 / TiO 2 Powder (V 2 O 5 -WO 3 / TiO 2The mass ratio is 1.9%-4.0% / 94.1% respectively) dispersed in 49 parts of dimethylformamide (DMF, CAS: 68-12-2) to form a solution A, and then 1 part of silica sol with a solid content of 40% is added to the solution A to form a mixed solution B, and the mixed solution B is ground for 2 hours using a sand mill to obtain a catalyst active powder slurry; the modified cordierite skeleton after drying in step 1 is immersed in the catalyst active powder slurry for 10 minutes to obtain a catalyst precursor, and the hydrophobic modified catalyst active powder slurry impregnation is completed;
[0079] Step 3: Vacuum drying: The catalyst precursor obtained in step 2 is vacuum dried at a temperature of 75°C and a vacuum pressure of -0.03 MPa for 5 h;
[0080] Step 4: High temperature calcination: The catalyst precursor dried in step 3 is calcined in a sintering furnace, the maximum calcination temperature is 550°C, and the maximum calcination time is 2h.
[0081] Description of the above comparative proportions:
[0082] (1) Comparative Example 1 Compared with Example 1 and Example 2, the pretreatment liquid for the modified cordierite skeleton in Example 1 and Example 2 is replaced by the deionized water in Comparative Example 1 instead of the titanate solution;
[0083] (2) Comparative Example 2 Compared with Example 5, the hydrophobic group V in Example 5 2 O 5 -WO 3 / TiO 2 Powder (V 2 O 5 -WO 3 / TiO 2 The mass ratio is 1.9%-4.0% / 94.1%) and the organic solvent dimethylformamide (DMF, CAS: 68-12-2) is replaced by the hydrophilic group V in Comparative Example 2 2 O 5 -WO 3 / TiO 2 Powder (V 2 O 5 -WO 3 / TiO 2 The mass ratio is 1.9%-4.0% / 94.1%) and deionized water.
[0084] Description of the above embodiments:
[0085] (1) Example 1 and Example 2. Compared with Example 1, Example 2 reduces the content of the titanate mixture in the modified cordierite skeleton titanate pretreatment solution in step 1;
[0086] (2) Example 2 and Example 3. Compared with Example 2, Example 3 increases the content of hydrophobic catalyst active powder in the catalyst active powder slurry in step 2;
[0087] (3) Example 3 and Example 4. Compared with Example 3, Example 4 replaces the isopropyl di(dioctylphosphite acyloxy) titanate in the modified cordierite skeleton titanate pretreatment solution in step 1 of Example 3 with isopropyl trioleyl titanate;
[0088] (4) Example 4 and Example 5. Compared with Example 4, Example 5 reduces the pore volume of the modified cordierite skeleton in step 1 of Example 4;
[0089] (5) Example 6 and Example 5. In Example 6, compared with Example 5, the number of pores in the modified cordierite skeleton is increased from 80 pores to 108 pores.
[0090] Refer to the denitrification activity detection method in DL / T1286-2021 "Technical Specifications for Denitrification Catalyst Detection in Thermal Power Plant Flue Gas", where the denitrification activity test conditions are: flue gas temperature 350°C, catalyst test space velocity 150000h - , catalyst test area velocity 23m / h, test inlet NOx concentration 500mg / Nm 3 , test inlet SO2 concentration 6500mg / Nm 3 .
[0091] Refer to the detection method of the mass shedding rate of the catalytic layer in XB / T607-2011 "Test Methods for Coating Materials of Gasoline Vehicle Exhaust Purification Catalysts".
[0092] The performance indicators of the catalysts prepared in the above examples and comparative examples are as follows:
[0093]
Claims
1. A method for preparing a high space velocity SCR denitration catalyst for a gas generator set, characterized in that: The following steps are involved: Step 1: pretreatment of the cordierite skeleton: soaking the modified cordierite skeleton in a titanate compound solution, and then drying the soaked modified cordierite; Step 2: Impregnation of catalyst active powder slurry: impregnating the modified cordierite skeleton dried in step 1 with hydrophobically modified catalyst active powder slurry to obtain a catalyst precursor, wherein the catalyst active powder slurry contains 35% to 50% of hydrophobically modified catalyst powder, 1% to 3% of silica sol and 43% to 64% of an organic solvent; Step 3: vacuum drying: vacuum drying the catalyst precursor obtained in step 2; Step 4: high temperature calcination: calcine the catalyst precursor dried in step 3 to obtain a high space velocity SCR denitration catalyst; Wherein, the modified cordierite skeleton is a honeycomb with 80 to 108 pores, and the pore volume of the modified cordierite skeleton is 0.05 to 0.2 ml / g; The mass ratio of the titanate compound in the titanate compound solution is 60% to 80%; the titanate compound is one of isopropyl di(dioctylphosphite) titanate or isopropyl trioleyl titanate.
2. The method for preparing a high space velocity SCR denitration catalyst for a gas power generation unit according to claim 1, characterized in that: In step 1, a titanate compound is dissolved in deionized water to form a titanate compound solution, and the modified cordierite skeleton is immersed in the titanate compound solution for 2 hours. Then, the modified cordierite skeleton is taken out and dried at 110° C. for 3 hours.
3. The method for preparing a high space velocity SCR denitration catalyst for a gas power generation unit according to claim 1, characterized in that: The modified cordierite framework contains 5.5% of MgO, 13.5% of Al2O3 and 81% of SiO2 in mass percentage.
4. The method for preparing a high space velocity SCR denitration catalyst for a gas power generation unit according to claim 1, characterized in that: The step 2 also includes a step of preparing a catalyst active powder slurry: The hydrophobically modified catalyst active powder was weighed, dispersed in an organic solvent and stirred for 1 hour to form a solution A, and then silica sol was added to the solution A to form a mixed solution B. The mixed solution B was ground for 2 hours to obtain a catalyst active powder slurry.
5. The method for preparing a high space velocity SCR denitration catalyst for a gas power generation unit according to claim 1 or 4, characterized in that: The hydrophobic modified catalyst active powder is hydrophobic V2O5-WO3 / TiO2 powder, and the mass percentages of V2O5, WO3 and TiO2 are 1.9%, 4.0% and 94.1% respectively; the silica sol is alkaline silica sol, and the solid content of the silica sol is 40%; the organic solvent is dimethylformamide.
6. The method for preparing a high space velocity SCR denitration catalyst for a gas power generation unit according to claim 1, characterized in that: In step three, the volatile organic solvent is condensed by a condensation device; the vacuum drying temperature is 75° C., the vacuum pressure is -0.03 MPa, and the vacuum drying time is 5 hours.
7. The method for preparing a high space velocity SCR denitration catalyst for a gas power generation unit according to claim 1, characterized in that: In step 4, the maximum calcination temperature is 550° C., and the maximum calcination time is 2 hours.
8. A high space velocity SCR denitration catalyst for a gas generator set, characterized in that: The preparation is obtained by the preparation method as described in any one of claims 1 to 7.
Citation Information
Patent Citations
Inorganic artificial stone made of aluminum ash and waste residues, and manufacturing method thereof
CN109206080A
